Inovasi Produk sebagai Variabel Mediasi Pengaruh Orientasi Pasar dan Orientasi Kewirausahaan dalam Meningkatkan Keunggulan Bersaing Sektor UMKM Olahan Ikan Patin di Kampung Patin, Desa Koto Mesjid, Kecamatan XIII Koto Kampar - Mashur Fadli; Meyzi Heriyanto; Kasmirudin Kasmirudin; Lie Othman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
variables on strategies to increase competitive advantage in the Catfish Processed MSME Sector in Patin Village, Koto Mesjid Village, District XIII Koto Kampar. The study used a quantitative approach where primary data was collected through a survey of 70 respondents and the statistical technique Partial Least Square (PLS) was used to process the data. The results of the study confirm that there is a significant effect of market orientation on product innovation and competitive advantage, both direct and indirect effects through the mediation of product innovation variables. The entrepreneurial orientation variable influences the product innovation variable and competitive advantage, either directly or indirectly through the product innovation variable, but some other factors or variables affect the competitive advantage variable.